PENGARUH MODEL PEMBELAJARAN DISCOVERY LEARNING TERHADAP PRESTASI BELAJAR PADA MATA PELAJARAN IPAS PESERTA DIDIK KELAS V SD NEGERI 1 TONJA DENPASAR - Ni Made Maharani; Ni Made Anggreni; Gusti Ayu Dewi Setiawati (JURNAL ILMIAH NUSANTARA, 2026)
This study aims to determine the effect of the Discovery Learning learning model on students’ achievement in IPAS subjects for fifth-grade students at SD Negeri 1 Tonja Denpasar. This study was motivated by the low learning achievement of students caused by teacher-centered learning activities, resulting in students being less active in discovering concepts independently. This study used a quantitative approach with a quasi-experimental design. The population consisted of all fifth-grade students of SD Negeri 1 Tonja Denpasar totaling 60 students. The sample was selected using simple random sampling techniques. Data collection techniques included observation, documentation, and learning achievement tests. The data were analyzed using descriptive and inferential statistics with the t-test. The results showed that the Discovery Learning model had a significant effect on students’ learning achievement in IPAS subjects. Students who learned through the Discovery Learning model achieved higher learning outcomes than students who learned through conventional learning models.